The performance of concrete exposed to marine environments: Predictive modelling and use of laboratory/on site test methods. (15th September 2015) - Nanukuttan, S.V.; Basheer, P.A.M.; McCarter, W.J.; Tang, L.; Holmes, N.; Chrisp, T.M.; Starrs, G.; Magee, B.
Highlights: Suitability, scope and repeatability of test methods in assessing chloride ingress. Beneficial features of Permit ion migration test for on site assessment of concrete. 20 years of chloride ingress data from a marine structure. Modelling the chloride ingress into concrete and validation of modelling. A methodology for developing performance-based specifications for concrete. Abstract: This paper reports an approach by which laboratory based testing and numerical modelling can be combined to predict the long term performance of a range of concretes exposed to marine environments. Firstly, a critical review of the test methods for assessing the chloride penetration resistance of concrete is given. The repeatability of the different test results is also included. In addition to the test methods, a numerical simulation model is used to explore the test data further to obtain long-term chloride ingress trends. The combined use of testing and modelling is validated with the help of long-term chloride ingress data from a North Sea exposure site. In summary, the paper outlines a methodology for determining the long term performance of concrete in marine environments.